Development of English Vocabulary Based on Sasak Language of Meno Mene As A Media In English - Hendi, Muhamad; Herman, Herman; Martini, Sri (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2023)
The aims of this study is to analyze the development of English vocabularies by using language of Sasak Meno Mene dialectic conducting a teaching learning process between the English teacher and the students. This study is utilized a quantitative descriptive to analyze the study. The instruments in collecting the data were employed of a questionnaire, observation, and documentation. The populations of this research are 36 students of class X that consist of 20 female and 16 male.The research was applied in Madrasah AliyahTahziulAkhlakSisik, Pringgarata, central Lombok. The results of the study shows thatthe development of word based on the sasak language can be development based on the correlation coefficient (r count), the value of r count is 0.344. This thing can happen because there is a motivation from the teacher and the researcher to the students in the classroom setting on how to the use of Sasaklanguage in comprehending of vocabularies mastery.Therefore, the English teacher may applyof using sasak language as Method in teaching English process. Because it can make the English learning process more enjoyable, fun and effective.